Ability of General Dentists and Prosthodontists to Discern and Identify Incremental Increases in Occlusal Vertical Dimension in Dentate Subjects - Remiszewski, David; Bidra, Avinash S; Litt, Mark D (The International journal of prosthodontics, 2017)
The aim of this study was to determine whether dentists are able to discern and identify increases in occlusal vertical dimension (OVD) in dentate subjects without apparent loss of OVD. A total of 10 dentate subjects had mandibular overlays fabricated at 2-, 3-, 4-, and 5-mm openings of the anterior guide pin (AGP) of a semiadjustable articulator. Standardized frontal and profile photographs with subjects wearing each of the overlays were made. Photographs were presented in random order to 40 judges comprising 20 prosthodontists and 20 general dentists who were informed about the purpose of the study. Judges first rated the degree of facial naturalness on a visual analog scale (VAS) and then took a discriminatory sensory analysis test (triangle test) where they were required to correctly identify the image with no increase in OVD from a set of three images. Mean VAS ratings for facial naturalness were inversely correlated with incremental increases in OVD, irrespective of the judge's background. Though subjects were rated less natural with incremental increases in OVD, only a 5-mm increase from baseline was clinically significant (P < .05). For the triangle test, judges correctly identified the image with a 3-mm increase in OVD 57% of the time (P < .582), irrespective of the judge's profession, sex, race, and years in practice, which were clinically insignificant. Increasing OVD by a 5-mm opening of the AGP of the articulator significantly decreased the judge's evaluation of facial naturalness. The ratings were more pronounced in female subjects than in male subjects. However, an increase in OVD of 3 mm was visually indistinguishable by the judges.